Taxing informal sector through modified taxation: Implementation challenges and overcoming strategies - Paul Hammond; Paul Adjei Kwakwa; Daniel Berko; Edmond Amissah (Cogent Business & Management, 2023)
The informal sector often poses a measurable challenge to effective domestic revenue mobilization due to its peculiar characteristics. Modified taxation, which is a form of presumptive taxation, has been identified as an innovative way of taxing the informal sector. The study examines some of the possible implementation challenges of tax reform as well as identifying mitigating strategies to overcome the challenges. The best-worst method (BWM) of multi-criteria decision-making was employed in this study. Twenty potential challenges and 12 strategies were identified from the literature. Eight experts were contacted to rank the challenges and strategies for the implementation of the modified taxation. They were made to complete an online questionnaire by rating their preferred criteria over others. A linear BWM solver was used to determine the optimal weights of each category. The perception of tax administration emerged as the best-ranked potential obstacle to the practicability of the tax policy. On the strategy side, building trust in the taxpayers is the key to successful implementation.
Keywords: 650; best-worst method; challenge; informal sector; modified taxation; strategy